Differences in soil properties and the rates of decomposition of plant biomass on non-organically and organically managed soils - Pitaloka, Triana; Dulbari, Dulbari; Barus, Junita (Brawijaya University, 2025)
Organic farming has been advocated as a more environmentally sound and ecologically balanced alternative to the dominant agricultural model. This study compared the decomposition of plant biomass in organically and non-organically managed soil properties. The treatments consisted of non-organic land (A) and organic land (B). Non-organic land used chemical fertilizers as the main fertilizer, and organic fertilizers were not always given. In organic land, all fertilizers given were organic fertilizers, and organic pesticides have been carried out over the last five years. The area of ??each land studied was approximately 1,000 m2 divided into five points diagonally. Observations were made on soil pH, organic C, total N, and P Bray, as well as the amount and weight of soil macrofauna. The decomposition rate of the dried Edamame soybean biomass in the soil was estimated using the litterbag method. A litterbag measuring 30 x 20 cm with a pore size of 2-3 mm was used for this study. Seventy grams of plant biomass were put into the litterbag and buried in the soil to a depth of 10-20 cm. Analysis of C and N contents in plant biomass was carried out before and after incubation in the soil. The results showed that soil chemical properties are better, and soil macrofauna is more abundant in organic than non-organic land. Soil fertility in organic land was characterized by a larger decomposition rate constant (k) and a faster decrease in C/N ratios. The decomposition rate constant (k) in organic soil was 0.171, and that in non-organic soil was 0.105.